Reflections on War in Creative Context of Design Education in Ukraine - Radomska, Violetta; Ponkalo, Solomiia (Journal of Education Culture and Society, 2023)
Aim. The aim of the research is focused on the analysis and determination of changes and priorities in the Ukrainian artistic and design discourse of education as inspired by the military actions in Ukraine in 2022–2023.Concept. The research materials are inspired by the basic concept of practical application of motivational aspects in modern design education. The outlined areas of research are aimed at refuting the stereotype of negative intentions in the subconscious perception of full-scale military operations.Results. The results of the dynamics of formal and conceptual priorities in the design of students in the conditions of the liberation war in Ukraine were obtained. Monitoring data is an essential basis for improving innovative, and most importantly, creative and variable pedagogical practice, which makes it possible to comprehensively implement it in the authoritative administrative state hierarchy.Conclusion. The results of the monitoring demonstrated the experience of the creative potential of the students of the Department of Design and Architecture Fundamentals (DOA) in difficult social and political conditions, which is directed to the positive aspects of the future victory.Practical application. The study will contribute to the improvement of the structural and logical schemes of educational and professional programs Environmental Design in the system of art and design education. A variable approach will contribute to the establishment of landmarks of cultural identity, the implementation of new creative ideas for the development of modern Ukrainian design for the purposes of state building.